2020
DOI: 10.20448/journal.501.2020.71.74.90
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Monetary Transmission Mechanism in Nigeria (1986-2017)

Abstract: This study explored the impacts of the different aspects of financial development on monetary transmission mechanism in Nigeria from the period of 1986-2017 using quarterly data. Variables such as broad money supply, debt stock, stock market capitalization, stock market value traded, total deposit money bank's asset, total financial assets, private sector credit, inflation rate, monetary policy rate, exchange rate, all share index and output, were used to carry out this investigation. The study adopted Pesaran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The study found a positive influence of trade intensity on the convergence process and believed that the initial asymmetric nature of the business cycles of West African countries does not represent a hindrance to the convergence process. Furthermore, Oyadeyi and Akinbobola (2020) were of the view that global shocks affect the monetary policy transmission of developing countries. These results were corroborated by other studies, such as Oyadeyi (2022aOyadeyi ( , 2023a and Oyadeyi and Akinbobola (2022).…”
Section: Empirical Issues On Monetary Integrationmentioning
confidence: 99%
“…The study found a positive influence of trade intensity on the convergence process and believed that the initial asymmetric nature of the business cycles of West African countries does not represent a hindrance to the convergence process. Furthermore, Oyadeyi and Akinbobola (2020) were of the view that global shocks affect the monetary policy transmission of developing countries. These results were corroborated by other studies, such as Oyadeyi (2022aOyadeyi ( , 2023a and Oyadeyi and Akinbobola (2022).…”
Section: Empirical Issues On Monetary Integrationmentioning
confidence: 99%
“…The study also showed that, albeit in a limited way, policy rates in Ghana react to the expansion of mobile money. In Nigeria, Olajide and Temidayo's [3] study uses quarterly data to examine the effects of several components of financial development on the monetary transmission mechanism in Nigeria from 1986 to 2017. The findings revealed that financial development indicators and their interactions with the policy rate had various degrees of impact on each channel of monetary policy.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…A well-developed financial system can attract more foreign investors, which can increase demand for the local currency and help stabilize the exchange rate. Additionally, a more efficient financial system can enable firms to better hedge against exchange rate risk, reducing volatility in the foreign exchange market [3].…”
Section: Introductionmentioning
confidence: 99%